MIMO Techniques in Wireless Communications Systems - the Basics for E-learning Technology Implementation - Dang, Truong Son; Phan, Hong Phuong (Journal of Technical Education Science, 2009)
Nowadays wireless communications has been studied and developed very fast in all over the world and is the basics of e-learning technologies for improving the quality of education and extending its reach to broader audiences. This paper introduces an effective approach for increasing capacity and speed of a wireless communication system – application of MIMO techniques (multiple-input multiple-output) used in Wireless LAN (IEEE 802.11n) and WiMAX (IEEE 802.16) focusing on the procedure of modelling a MIMO channel. A Matlab program developed by the authors is presented to calculate correlation matrix of the channel according to three types of Power Azimuth Spectrum in one-cluster and multiple-cluster propagation cases.